STUDI KETERSEDIAAN SUMBERDAYA AIR UNTUK MEMENUHI KEBUTUHAN AIR BERSIH DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , Joko Triyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing population resulted in an increased water demand. Yogyakarta City, Sleman District, and Bantul District has been experience water deficits in 2010 reach 1,288 liters/sec and will be happen in 2015 and 2030 reaches 1,330 and 1,750 liters/sec. attempt to find the source of raw water should be done to meet of water demand. The first alternative is to take raw water from Progo River. The second alternative is to take raw water from springs at Magelang District. This study to get an description of the two sources of raw water, for that purpose were measuremented springs discharge at the end of the dry season, dependableflow analysis Q90 of Progo River, raw water transmission system simulated using Waternet Version 2.2 , calculated of the cost production with a full costing method, calculated of the investment cost and investment feasibility analysis by Benefit Cost Ratio (BCR) method. The results of this study indicate that the availability of water in five selected springs in Magelang regency of 1000 liters/sec, dependableflow Q90 of Progo River is 9,450 liters/sec, raw water from Magelang Regency allows to be transmitted to the Province of DIY by the gravity method, the production cost of water with source water from the springs in Magelang District is more efficient of IDR 280,934,386 from water sources Progo River, investment cost of Water Treatment Plant (WTP) with Progo River water source is more expensive IDR 2,048,147,800 than investment cost of raw water transmission from Magelang District. The annual profit from spring water source in Magelang District larger IDR 5,439,542,164/year than water source of Progo River.